2021
DOI: 10.1016/j.xpro.2021.100752
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and analysis of fractions enriched in WrappER-associated mitochondria from mouse liver

Abstract: Summary The endoplasmic reticulum (ER) plays a central role in lipid homeostasis, but the role of individual ER subdomains in lipid biology has not been elucidated. WrappER is a curved wrapping type of rough-ER that establishes extensive contacts with almost every mitochondria of the hepatocyte in the mouse liver. Here, we describe a protocol for isolation of fractions enriched in wrappER-associated mitochondria from the mouse liver. We also provide techniques for assessing its quality by electron m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…To gain insights into the effects of Synj2bp knockdown in hepatic metabolism, we performed quantitative proteomics analysis of the liver fractions enriched in wrap-pER-associated mitochondria (Fig. 2C and Additional file 2: Table S1) [42]. Compared to control fractions, WAM isolated from Synj2bp-silenced livers contained nearly half the amount of ER proteins (Fig.…”
Section: Upregulated Mitochondria Fatty Acid Respiration In Synj2bp-s...mentioning
confidence: 99%
See 2 more Smart Citations
“…To gain insights into the effects of Synj2bp knockdown in hepatic metabolism, we performed quantitative proteomics analysis of the liver fractions enriched in wrap-pER-associated mitochondria (Fig. 2C and Additional file 2: Table S1) [42]. Compared to control fractions, WAM isolated from Synj2bp-silenced livers contained nearly half the amount of ER proteins (Fig.…”
Section: Upregulated Mitochondria Fatty Acid Respiration In Synj2bp-s...mentioning
confidence: 99%
“…WAM-enriched fractions were isolated as described [42]. Briefly, the mouse liver was quickly excided, washed three times with Buffer A (BA; 10 mM Tris-HCl, 1 mM MgCl 2 , 0.1 mM EGTA, pH 7.4) supplemented with 250 mM Sucrose (B10), minced in small pieces, and resuspended in 5 ml B10 supplemented with 1 × Protease Inhibitor Cocktail (PIC; Thermo Fisher Scientific, #78429).…”
Section: Preparation Of Fractions Enriched In Wrapper-associated Mito...mentioning
confidence: 99%
See 1 more Smart Citation
“…These changes in sphericity and morphology may impact the ability of mitochondria to form contact sites. Particularly, liver mitochondria are known to exhibit phenotypes in which ER wraps around them, known as wrappER, to modulate lipid flux (63)(64)(65). To investigate this paradigm, we qualitatively identified wrappER within liver tissue (Figures 3G-H).…”
Section: Ultrastructural Changes In Murine Liver Reveals Aging Is Ass...mentioning
confidence: 99%
“…Qualitatively, we found that wrappER exists in both 3-month and 2-year murine liver tissue (Figures 3G'-H'), but in 3-month tissue wrappER contact is much more extensive (Figures 3G"-H"). This suggests that liver lipid homeostasis may be negatively impacted (63)(64)(65). However, to confirm these changes and further explore the implications of these mitochondrial morphological alterations, we analyzed metabolism and performed lipidomics in mice.…”
Section: Ultrastructural Changes In Murine Liver Reveals Aging Is Ass...mentioning
confidence: 99%